Teaching Foundations for Professional Orientation in a Pedagogical University (Eurasian Scientific Herald, 2023)
This article examines and analyzes the ethics of teaching the basics of vocational orientation at the teacher training college. This information plays a crucial role in the training of prospective teachers at teacher training colleges. These universities provide comprehensive education and training for prospective professionals who are committed to making educational changes. One of the most important components of this training is the basics of pedagogical career orientation